Lecturers’ Strategy in Teaching English for Specific Purposes to Islamic Banking Students - Kurniawan, Yuda Septian; Permana, Dio Resta (Universitas Indo Global Mandiri, 2025)
This study aimed to identify and analyze the strategies used by lecturers in teaching English for Specific Purposes (ESP). The object of the study was English lecturers teaching English Banking courses to 6th semester students of the Islamic Banking study program at the Nahdlatul Ulama College of Sharia Economics, Bengkulu. This study employed descriptive qualitative research that explores learning models, methods, and materials that suit the needs of students in the field of Islamic banking. The data collection techniques were observation, in-depth interviews, and documentation. The research findings showed that lecturers tended to adapt various teaching strategies that integrate communicative approaches, task-based learning, and the use of authentic materials relevant to the world of Islamic banking. In addition, collaborative approaches such as group discussions, simulations of banking service practices, and real case studies were also implemented to increase students' active participation. This teaching model was not only oriented to the mastery of language structures, but also to professional communication competencies that were in accordance with the work context and industry needs. The results showed that context-based learning, problem-based learning, and collaborative methods were the most effective strategies. Integration of Islamic banking content in English materials increases student participation and understanding. This study also recommends the development of an ESP curriculum that is more integrated with the expertise competencies of the study program, as well as continuous training for lecturers who teach the course to enable them to manage innovative, contextual, and responsive learning that meets the needs of the times. Keywords: English for Specific Purpose, Islamic Banking Students, Lecturer's Teaching Strategy